2003
DOI: 10.1124/jpet.102.042648
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Implications of Brown Adipose Tissue Proliferation in Rats and Monkeys Treated with the Thiazolidinedione Darglitazone, a Potent Peroxisome Proliferator-Activated Receptor-γ Agonist

Abstract: Thiazolidinediones represent an established class of insulin sensitizing agents for treating noninsulin-dependent diabetes mellitus. Darglitazone, a thiazolidinedione approximately 200ϫ more potent than ciglitazone, was evaluated in preclinical safety assessment studies using rats (1, 5, and 50 mg/kg/day) and cynomolgus monkeys (50, 75, and 100 mg/kg/day). Darglitazone was a potent adipogenic agent in rats, causing hyperplastic/hypertrophic changes and firmness of white and perirenal, dorsal thoracic (TBAT), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Only one such study was conducted in diabetic mice, showing a suppression of proinflammatory gene expression and reduction in infarct size (Tureyen et al, 2007). Darglitazone is a TZD that is 20 to 150 times more g-receptor-selective than either rosiglitazone or pioglitazone, and is almost 10 times more orally potent in restoring euglycemia (Aleo et al, 2003;Oakes et al, 2001). Thus, the objectives of the current study were to investigate the effects of darglitazone treatment on H/I insult in the diabetic ob/ob mice with specific attention to the acute inflammatory response(s).…”
Section: Introductionmentioning
confidence: 99%
“…Only one such study was conducted in diabetic mice, showing a suppression of proinflammatory gene expression and reduction in infarct size (Tureyen et al, 2007). Darglitazone is a TZD that is 20 to 150 times more g-receptor-selective than either rosiglitazone or pioglitazone, and is almost 10 times more orally potent in restoring euglycemia (Aleo et al, 2003;Oakes et al, 2001). Thus, the objectives of the current study were to investigate the effects of darglitazone treatment on H/I insult in the diabetic ob/ob mice with specific attention to the acute inflammatory response(s).…”
Section: Introductionmentioning
confidence: 99%
“…However, both in pharmacological and clinical use, TZDs increase adiposity and body weight, and elicit clinical side effects including edema, plasma volume expansion, and hemodilution (Aleo et al, 2003;Schöfl and Lü bben, 2003;Yang et al, 2003). These drawbacks stimulate the search for PPAR␥ modulators with modified pharmacological profiles that regulate fatty acids and glucose metabolism with a reduced increase in adiposity, since this undesirable effect may favor the development of obesity, a risk factor often associated with insulin resistance (Oberfield et al, 1999).…”
mentioning
confidence: 99%
“…Tornvig et al first showed that troglitazone increased marrow adiposity in the Apoe -/-strain, but no changes in bone mass were observed in these mice [16]. Darglitazone is 20 times more potent than rosiglitazone and 150 times more potent than pioglitazone [17]. A dose of 10 mg/(kg day) in 8-month-old male mice resulted in a profound decrease in both trabecular and cortical bone [18], but the effect of this TZD on marrow adiposity was not reported.…”
Section: Pparc Fat and Bonementioning
confidence: 93%